2004
DOI: 10.1248/cpb.52.1091
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antiviral Fucoidan from Sporophyll of Undaria pinnatifida (Mekabu)

Abstract: Blown algae like wakame (Undaria pinnatifida) and kombu (Laminaria sp.) are popular foods in East Asia. These edible algae have been used as rich sources of minerals, vitamins and dietary fibers. They have been attracted recently as multifunctional foods for maintaining our health.Fucoidan (fucan sulfate) is a fucose-containing sulfated polysaccharide from brown algae such as Fucus vesiculosus, 1) Ecklonia kurome, 2) and Cladosiphon okamuranus.3) Fucoidans showed various biological activities like anticoagulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
141
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(152 citation statements)
references
References 15 publications
7
141
1
3
Order By: Relevance
“…Fucoidans are sulphated polysaccharides extracted from the cell wall of various species of brown seaweeds (Berteau and Mulloy, 2003). Fucoidans have been shown to have antitumour (Zhuang et al, 1995), antiviral (Lee et al, 2004) and antibacterial (McClure et al, 1992) properties. Overall, laminarin and fucoidan may offer a dietary means to modulate the gut environment and/or modulate immunity, thereby reducing the risk of diarrhoea and promoting productivity in the absence of in-feed antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans are sulphated polysaccharides extracted from the cell wall of various species of brown seaweeds (Berteau and Mulloy, 2003). Fucoidans have been shown to have antitumour (Zhuang et al, 1995), antiviral (Lee et al, 2004) and antibacterial (McClure et al, 1992) properties. Overall, laminarin and fucoidan may offer a dietary means to modulate the gut environment and/or modulate immunity, thereby reducing the risk of diarrhoea and promoting productivity in the absence of in-feed antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans, the family of sulphated heteropolysaccharides, are composed mainly of a-1,3-linked L-fucose residues (Percival and Mc Dowell, 1967). Fucoidans have been shown to have antitumour (Zhuang et al, 1995), antiviral (Lee et al, 2004) and antibacterial (McClure et al, 1992) properties. Reilly et al (2008) showed that a combination of fucoidan and laminarin increased the volatile fatty acid (VFA) concentration in the colon of weaned pigs, indicating that these fractions were fermented by the microbial population in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of synthesized and algae-derived sulfated polysaccharides such as dextran sulfate, fucoidan, spirulan, and hornan have been reported to be antiviral components. [12][13][14][15][16][17][18][19] Some sulfated polysaccharides are known to inhibit both virus binding and penetration processes in the early phase of virus-cell interactions. In the present study, dextran sulfate was shown to have inhibitory effects on these two processes.…”
Section: Discussionmentioning
confidence: 99%